Performance investigation of adding clean hydrogen to natural gas for better sustainability - Ishaq, H.; Dincer, I (ELSEVIER SCI LTD, 2020)
This paper presents a novel system of adding clean hydrogen to the natural gas for more effective and more efficient combustion. The proposed system includes a wind-photovoltaic hybrid system where both wind and solar energy sources are simultaneously utilized. A partial amount of electrical power produced by the wind turbines, PEM fuel cell and PV array is fed to the PEM electrolyser while the additional electricity is supplied to the community for use. In the hydrogen-natural gas blends, the fraction of hydrogen is taken from 0% to 20%, respectively, and the natural gas is reduced from 100% to 80% simultaneously to explore hydrogen addition effect in the combustion process. Although natural gas is cleaner than other fossil fuels, adding hydrogen to the natural gas makes it much cleaner and more environmental friendly. The blends of natural gas and hydrogen helps increase the combustion efficiency, decrease oxygen and reduce the emissions, in particular CO2. The results further reveal that the energetic efficiency of the combustion unit rises from 84.83% to 94.83% while the exergetic efficiency rises from 62.52% to 70.16% with the rise in hydrogen fraction from 0% to 20%. It is also found that the CO2 emissions decrease with the rise in hydrogen fraction in hydrogen-natural gas blends.
Keywords: Natural gas; Hydrogen; Wind energy; Solar energy; Combustion; Efficiency; ENERGY; OPTIMIZATION; EMISSIONS; ENGINES; BLENDS; Energy & Fuels; Engineering